EFFECT OF THRESHOLD VOLTAGE AND CHANNEL LENGTH ON DRAIN CURRENT OF SILICON N-MOSFET - Bakibillah, A.S.M.; Rahman, Nazibur (European Scientific Journal, ESJ, 2015)
This paper investigates the effect of threshold voltage on drain current for different channel lengths and analyses the impact of short channel on threshold voltage for Silicon n-MOS at room temperature. For characterization, n-MOS model N08 is used where the short channel length and width of 0.8μm and 10μm and long channel length and width of 20μm and 200μm are chosen. The simulation is accomplished using LTSPICE and the data is analysed and characterized using MatLab. For both cases it is found a significant increase in drain current. Therefore, threshold voltage and channel length has substantial effect on drain current i.e. on device Id-Vds and Id-Vgs characteristics.